Target costs and reduce production costs kayzen calculation methods . (Journal of Economic Research & Business Administration, 2015)
In this article, modern management accounting system - target costing and Kaizen methods . Target costing and important aspects determine the calculation methods kayzenanalyzed. Emphasis in Japan to control the life cycle of a consumer product companies that pay depends on the efficient use of these two systems.
Keywords: enterprise